BAHAN AJAR TEMATIK INTEGRATIF KEARIFAN LOKAL BERBASIS KVISOFT FLIPBOOK MAKER UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD - Harjanto, Ambyah; Suroto, Suroto; Sumargono, Sumargono; Efendi, Jodi Sofyan (Lentera: Jurnal Ilmiah Kependidikan, 2021)
This study aims to test the effectiveness of thematic integrative teaching materials based on local wisdom in elementary schools. The method used in this research is an experimental research method. The population in this study were Elementary School Students (SD) in Bandar Lampung City. The results showed significant differences between the practical and control classes after being given different lessons. The mean value of the experimental class learning outcomes = 87.07> the mean value of the control class learning outcomes = 75.82. The Experiment Class (using Integrative Thematic Teaching Materials of Local Wisdom Based on Kvisoft Flipbook Maker) was higher than the Control Class (using Ordinary Teaching Materials). Learning using Integrative Thematic Teaching Materials of Local Wisdom Based on Kvisoft Flipbook Maker improves student learning outcomes.